The relationship between capital structure and firm performance: The moderating role of agency cost - Pranata, Robby; Nugroho, Vina (Institute of Computer Science (IOCS), 2025)
This research investigates the relationship between capital structure and financial performance, with a particular focus on the moderating influence of agency costs. It analyzes the impact of capital structure on financial outcomes through the perspective of agency costs. Data was obtained from non-financial firms listed on the Indonesia Stock Exchange (IDX) between 2020 and 2022. Capital structure is represented using metrics such as the debt-to-asset ratio and debt-to-market capitalization, while financial performance is measured through indicators like return on assets (ROA), Tobin’s Q, and earnings per share (EPS). The results reveal that, although capital structure can negatively influence financial performance, agency costs can serve as a positive moderating factor. By considering various performance metrics, the study highlights the significance of adopting a holistic approach to analyzing capital structure. The research aims to provide a deeper understanding of the dynamic interplay between capital structure and financial performance